2011
DOI: 10.1186/2047-783x-16-3-101
|View full text |Cite
|
Sign up to set email alerts
|

Cancer risk in HIV-infected individuals on HAART is largely attributed to oncogenic infections and state of immunocompetence

Abstract: ObjectivesTo estimate the cancer risk of HIV-infected patients in the HAART era with respect to a general reference population and to determine risk factors for malignancy.MethodsLong term (1996-2009) cancer incidence of the Bonn single centre HIV cohort was compared to the incidence of the reference population of Saarland using standardized incidence ratios (SIR). Poisson regression analysis was used to identify predictors of cancer risk.Results1,476 patients entered the cohort, enabling 8,772 person years of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 17 publications
3
19
0
1
Order By: Relevance
“…The Bonn cohort in Vogel et al . seems to be more similar to ours , with the risk in HIV‐infected patients in the Vogel et al . study being four times higher in men [SIR = 4.4 (95% CI 3.6–5.3)] and about three times higher in women [SIR = 2.5 (95% CI 1.4–3.9)], relative to the general population.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The Bonn cohort in Vogel et al . seems to be more similar to ours , with the risk in HIV‐infected patients in the Vogel et al . study being four times higher in men [SIR = 4.4 (95% CI 3.6–5.3)] and about three times higher in women [SIR = 2.5 (95% CI 1.4–3.9)], relative to the general population.…”
Section: Discussionsupporting
confidence: 91%
“…The old division between ADCs and NADCs has been widely used [1][2][3][4][5][6], and some recent studies divided malignancies into infection-related types and cancers unrelated to infectious diseases [25,26]. In this study, a categorization in which cancers were divided into ADCs, virusrelated NADCs and non-virus-related NADCs was used.…”
Section: Discussionmentioning
confidence: 99%
“…35 Of the 1476 patients entered into their study, they identified 114 patients with invasive cancers. As in other studies, malignancies associated with infectious agents [e.g.…”
Section: Anal Hpv Infection and Disease In Womenmentioning
confidence: 99%
“…[6] Whether genetic factor(s) play any role in the pathogenesis of thyroid cancers in HIV-positive patients is not clear. [4] Papillary thyroid carcinoma[7] and medullary thyroid carcinoma[8] were reported in advanced HIV positive patients. They were receiving antiretroviral therapy for HIV infection unlike our patient.…”
Section: Discussionmentioning
confidence: 99%